2017
DOI: 10.1370/afm.2122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Scribes on Physician Satisfaction, Patient Satisfaction, and Charting Efficiency: A Randomized Controlled Trial

Abstract: PURPOSE Scribes are increasingly being used in clinical practice despite a lack of high-quality evidence regarding their effects. Our objective was to evaluate the effect of medical scribes on physician satisfaction, patient satisfaction, and charting efficiency. METHODSWe conducted a randomized controlled trial in which physicians in an academic family medicine clinic were randomized to 1 week with a scribe then 1 week without a scribe for the course of 1 year. Scribes drafted all relevant documentation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
175
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(190 citation statements)
references
References 31 publications
(28 reference statements)
8
175
0
2
Order By: Relevance
“…20 The others were a quality improvement study not designed to create generalizable knowledge 18 and a research study that measured satisfaction with documentation time as a proxy for documentation time. 19 Thus, the impact of medical scribes on PCP productivity remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The others were a quality improvement study not designed to create generalizable knowledge 18 and a research study that measured satisfaction with documentation time as a proxy for documentation time. 19 Thus, the impact of medical scribes on PCP productivity remains unclear.…”
mentioning
confidence: 99%
“…21 Indeed, the only study examining time spent facing the patient, conducted in a cardiology clinic, found that providers spent more time facing the patient. 16 Data regarding the impact on patient satisfaction are more mixed, with some studies reporting improvement in patient satisfaction 22 , some reporting no change on all or most measures 17,19,23 , and some reporting reductions. 20 Only 2 of these studies were conducted in primary care 19,20 , of which 1 reported a high degree of comfort with scribes.…”
mentioning
confidence: 99%
“…13 Physicians were assigned a schedule of 1 week practicing with a scribe alternating with 1 week without a scribe. During the weeks when the physician was assigned a scribe, the scribe attended all patient encounters alongside the physician and drafted all relevant documentation, including the patient history, objective examination findings, assessment and plan, and patient instructions.…”
Section: Designmentioning
confidence: 99%
“…6,7 Recently, a randomized controlled trial of scribes found improvements in charting efficiency, overall physician satisfaction, and satisfaction with chart quality and accuracy. 8 Scribes could be especially valuable for academic physicians, whose teaching duties present an additional time burden on top of charting. While teaching students is enriching and enjoyable to many academic physicians, it can also result in higher stress and longer office days, cutting into both patient care time and personal time.…”
mentioning
confidence: 99%